Mid-infrared Bessel beams generation by subwavelength structure on quantum cascade laser - Tao, Jin (2013)
We proposed mid-infrared Bessel beams generation by subwavelength structure on quantum cascade laser. The result shows that the ring slit structure on the laser facet can realize zero order Bessel beam of first kind. Compared with Gaussian beam, the non-diffracting properties are demonstrated. The FWHM of the Bessel beam is smaller than the half of that of the Gaussian beam and can maintain over 45 mm and threshold current density is smaller than the half of that of the original unpatterned laser. The proposed structure may have applications for mid-infrared sensing and spectroscopy, and optical manipulations.